The role of the information environment during the first COVID-19 wave in Germany. Issue 1 (31st December 2022) - Stier, Sebastian; Weiß, Bernd; Hartmann, Timo; Flöck, Fabian; Breuer, Johannes; Schaurer, Ines; Kummerow, Mirjan
ABSTRACT: The COVID-19 pandemic has been accompanied by intense debates about the role of the information environment. On the one hand, citizens learn from public information campaigns and news coverage and supposedly adjust their behaviours accordingly; on the other, there are fears of widespread misinformation and its detrimental effects. Analyzing the posts of the most important German information providers published via Facebook, this paper first identifies a uniform salience of subtopics related to COVID-19 across different types of information sources that generally emphasized the threats to public health. Next, using a large survey conducted with German residents during the first COVID-19 wave in March 2020 we investigate how information exposure relates to perceptions, attitudes and behaviours concerning the pandemic. Regression analyses show that getting COVID-19-related information from a multitude of sources has a statistically significant and positive relationship with public health outcomes. These findings are consistent even across the ideological left/right spectrum and party preferences. These consistent correlational results demonstrate that during the first wave of COVID-19, a uniform information environment went hand in hand with a cautious public and widely accepted mitigation measures. Nonetheless, we discuss these findings against the backdrop of an increased politicization of public-health measures during later COVID-19 waves.